Cơ sở pháp lý cho hoạt động thông tin, thống kê khoa học và công nghệ - Nguyễn, Tiến Đức (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Presents systematically all existing legal regulations and documents, directly related to S&T Information, Statistics activities, having been issued from 1972 up to now.